One class of Nash equilibria in bimatrix games - Blaževič, Aneta Gracjana; Sūdžiūtė, Daina (Lietuvos matematikos rinkinys, 2002)
Active Nash equilibria existence in bimatrix game problem is reduced to the problem of nonexistence of special solutions of the systems (11) and (12).